CT and MRI in veterinary patients: an update on recent advances. Issue 10 (15th November 2013) - Labruyère, Julien; Schwarz, Tobias
Abstract : Computed tomography (CT) and magnetic resonance imaging (MRI) are two diagnostic imaging procedures that have become commonplace in first‐opinion practices. Both of these modalities are continually undergoing technological improvement and each has its advantages for different applications. This article provides an update on recent advances and compares the use of CT and MRI in different areas of the body.